Social Connection as a Public Health Issue: The Evidence and a Systemic Framework for Prioritizing the "Social" in Social Determinants of Health - Holt-Lunstad, Julianne (Annual review of public health, 2022)
There is growing interest in and renewed support for prioritizing social factors in public health both in the USA and globally. While there are multiple widely recognized social determinants of health, indicators of social connectedness (e.g., social capital, social support, social isolation, loneliness) are often noticeably absent from the discourse. This article provides an organizing framework for conceptualizing social connection and summarizes the cumulative evidence supporting its relevance for health, including epidemiological associations, pathways, and biological mechanisms. This evidence points to several implications for prioritizing social connection within solutions across sectors, where public health work, initiatives, and research play a key role in addressing gaps. Therefore, this review proposes a systemic framework for cross-sector action to identify missed opportunities and guide future investigation, intervention, practice, and policy on promoting social connection and health for all